2017
DOI: 10.3390/su10010061
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Assessing Alternative Land-Use Scenarios from the MOLAND Model: A Scenario-Based Impact Analysis Approach for the Evaluation of Rapid Rail Provisions and Urban Development in the Greater Dublin Region

Abstract: Abstract:In this study, environmental sustainability implications of planned rail infrastructure investments on the urban form and development in the Greater Dublin Region (GDR) have been analysed incorporating the scenario analysis approach. Various scenarios are developed using the MOLAND Model applications including: A baseline scenario incorporating a continuation of the present dispersed pattern of urban development and an alternative scenario with rail-oriented corridor development, under varying conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The mutual interaction of land use and transport has been widely documented [35][36][37][38] and models developed using these principles have been useful in the evaluation of policy and planning, such as the MEPLAN model for Leeds and Dortmund [39] and PECAS for Montgomery and Alberta [40,41]. For this paper, a cellular automata-based integrated land use transport model developed within the METRONAMICA framework by the Research Institute for Knowledge System (RIKS) [31] and used by amongst others [42][43][44][45][46][47] is presented here to show the relationship between land use and transport. This model was selected because the literature review revealed that there was a gap in both South African and African literature on the application and utilisation of a cellular automata (CA)-based land use transport model to understand urban dynamics, in that regard, METRONAMICA was an ideal model.…”
Section: The Metronamica Land Use Transport Model (M-lut)mentioning
confidence: 99%
“…The mutual interaction of land use and transport has been widely documented [35][36][37][38] and models developed using these principles have been useful in the evaluation of policy and planning, such as the MEPLAN model for Leeds and Dortmund [39] and PECAS for Montgomery and Alberta [40,41]. For this paper, a cellular automata-based integrated land use transport model developed within the METRONAMICA framework by the Research Institute for Knowledge System (RIKS) [31] and used by amongst others [42][43][44][45][46][47] is presented here to show the relationship between land use and transport. This model was selected because the literature review revealed that there was a gap in both South African and African literature on the application and utilisation of a cellular automata (CA)-based land use transport model to understand urban dynamics, in that regard, METRONAMICA was an ideal model.…”
Section: The Metronamica Land Use Transport Model (M-lut)mentioning
confidence: 99%
“…For instance, it evaluates the costs and benefits of transport provisions by carrying out empirical research in a given urban area in a specified time period. The examples can be found in Donaldson [29], Perl [30] and Ustaoglu et al [31,32]. The second group of literature derives indicators to measure and evaluate the costs and benefits of transport provisions.…”
Section: Assessing Sustainability Of Urban Form and Transport Relatiomentioning
confidence: 99%
“…They believe that street connectivity, density and development of mixed land-use, reduce the distance between destinations and can improve conditions for physical activity. Thus, these factors can promote active travel and increase the level of walking and cycling for both transport and recreational purposes (Ustaoglu et al, 2017).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Connected problems include the potential risk of noncommunicable diseases such as obesity (Abraído-Lanza, Shelton, Martins, & Crookes, 2017; Thurber et al, 2018), type 2 diabetes, cardiovascular disease (Abraído-Lanza et al, 2017), cancers and mental illnesses (Fakhrzadeh et al, 2016; Kim et al, 2016; Lawrence, Engelke, & Schmid, 2017; Ustaoglu, Williams, Petrov, Shahumyan, & van Delden, 2017). According to the statistics, physical inactivity and lack of mobility are associated with a 21% to 27% increased risk of colon cancer, a 27% increased risk of diabetes and heart disease, and a 30% increased risk of cardiovascular disease (John et al, 2017; Tabatabaei, Ardabili, Haghdoost, Nakhaee, & Shams, 2017).…”
Section: Introductionmentioning
confidence: 99%